Hubungan Pengetahuan dan Dukungan Suami dengan Ibu Hamil Memeriksakan Haemoglobin di Puskesmas Siak - Mawaddah, Mawaddah; Lubis, Dumasari; Parmin, Joria (Evidence Midwifery Journal, 2022)
Examination of the blood hemoglobin level of pregnant women is carried out at least once in the first trimester and third. Based on the report from the Riau Provincial Health Office in 2018, the hemoglobin examination rate for pregnant women was 67.72%, only 9.3% of pregnant women had hemoglobin examinations.The purpose of this study was to determine the relationship between knowledge and husband's supportwith pregnant women checking for hemoglobin at the Siak Health Center.The research design was cross sectional. The population of this study were all pregnant women in the first and third trimesters, with a sample of as many as 54 people, sampling technique accidental sampling. The measuring instrument used isquestionnaire. Univariate analysis is known most of the respondents with less knowledge as many as 29 people (53.7%) good as many as 25 people (46.3%), respondents who stated that their husbands did not support as many as 29 people (27.3%), husbands supported as many as 25 people (46.3%). Bivariate results are known tthere connection knowledge P value 0.016 POR (5,200) and known tthere husband's support relationship P value 0.003 POR(7,955)by checking hemoglobin in pregnant women at the Siak Health Center.It is hoped that health workers can provide information about the importance of conducting Hb checks on pregnant women and increasing knowledge of pregnant women through outreach activities in Maternity Classes and health facilities.